An Empirical Study of Reverse Logistics in Natural Cosmetic Products on Consumer Satisfaction - Resista Vikaliana; Fatih Wahid Satrio (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
This study aims to analyze the influence of reverse logistics on consumer satisfaction with cosmetic products at PT Nectars Natura Karya. Reverse logistics, which involves the management of product returns for recycling, repairs, or waste handling, is a crucial element in enhancing sustainability while meeting the expectations of modern consumers. The study employs a simple linear regression analysis method to understand the relationship between reverse logistics as the independent variable and consumer satisfaction as the dependent variable. Data were collected through questionnaires distributed to consumers of PT Nectars Natura Karya's best-selling product, Tamanu Daycream. Based on the simple linear regression test results, the simple linear regression equation obtained is Y = 0.666 + 0.464X, indicating that if the reverse logistics variable is zero or constant, consumer satisfaction increases by 0.666 units. The coefficient value for the reverse logistics variable is 0.464, meaning that a one-unit increase in reverse logistics will increase consumer satisfaction by 0.464 units or 46.4%. Furthermore, the R value (correlation coefficient) is 0.876, signifying a very strong relationship between reverse logistics and consumer satisfaction. The R2 value (coefficient of determination) is 0.767, indicating that 76.7% of the variation in consumer satisfaction can be explained by reverse logistics in the model, while the remaining 23.3% is explained by other factors outside the model. With an R2 of 0.767, the model is categorized as substantial, implying a very strong relationship between reverse logistics and consumer satisfaction. In the hypothesis testing, the t_calculated value of 17.778 far exceeds the t_table value of 1.664. Thus, H0 is rejected, and Ha is accepted, confirming that the relationship between reverse logistics and consumer satisfaction is highly significant.